THE INFLUENCE OF HEALTH EDUCATION BY SNAKES AND LADDERS GAME TOWARD KNOWLEDGE LEVEL ABOUT COMPLICATIONS PREVENTION AMONG HIGH RISK PREGNANT WOMEN AT FIRST TRIMESTER - Meisya Alfia Rosada; Tuti Sukini; Ribkha Itha Idhayanti (Poltekkes Kemenkes Semarang, 2019)
Background: During the first trimester of pregnancy prenatal care, detection and prevention of complications need to be done so that it can be addressed immediately. In preventing pregnancy complications, midwives are expected to act as facilitators and can build persuasive communication. One strategy of midwives in building persuasive communication is by providing health education.Purpose: The purpose of this study was to determine the effect of health education by snakes and ladders game toward knowledge level about complications prevention among high risk pregnant women at first trimester.Methods: This research was conducted in the working area of Kedu Community Health Center-Temanggung Regency. The study was Pre Experimental design with One Group Pretest Posttest. The population was pregnant women at high risk of first trimester. Saturated sampling was done, leading to 34 respondents. Wilcoxon test was applied with p0.05.Results : The test resulted in p value of 0.000 ( 0.05). It meant that health education by using snakes and ladders game influenced the knowledge level about complications prevention among high risk pregnant women at first trimester.Conclusion: It can be infered that knowledge level about complications prevention was influenced by health education by using snakes and ladders game. Snakes and ladders game can be chosen as a way of health education that can increase the activity of participants.